If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2 * 0 = -6 Multiply -2 * 0 x + 0 = -6 Anything times zero is zero. x + 0 = -6 Reorder the terms: 0 + x = -6 Remove the zero: x = -6 Solving x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = -6
| -16x^2+22x+100=80 | | -2(7x+1)=6(1-3x)+2 | | 9=y/x | | -(3y+2)-(-2y-4)=-3 | | 4B-7=15 | | 4AB-7A=15A | | 9=x/y | | 36x^2=3600 | | a+6/3=a/2 | | Y=-3/5x+7 | | 4y-9-5y+12=0 | | 3x+4x=-77 | | 2(2-x)=3(4-2x) | | 4+y=-5 | | x/4+1=x | | 15x+(x^2)=64 | | Cx-9x=5 | | .5x(2x-6)=-6 | | 5(x-4)=55 | | 3/10x+14.8=21.2 | | 6x+2x-8=5x-17 | | 1/2t-3.99=4.76 | | 3n-6=-21 | | 9x+29=6x+77 | | 5/6*x-1/5*x+4=7/10*x | | 2x^2+3x^2=144 | | 2a^2+36=18 | | 6=1+4X+x | | -9x+45=x+22.5 | | 18+9d=12d | | 10t+17=-17+12t | | 4x^2-y^2=256 |